Focal dermal hypoplasia: Unusual presentation in Saudi Arabia - Awadh Alamri; Mazin Al Jabri (Wolters Kluwer Medknow Publications, 2016)
Focal dermal hypoplasia (Goltz syndrome) is a rare genetic multisystem characterized by multiple abnormalities of ectodermal and mesodermal origin. It is found predominantly in females. We report a case of a two month-old baby girl who had dermal hypoplasia, atrophic skin lesions with telangiectasia in a linear pattern, fat herniations, papillomas and cleft of the upper lip, ectrodactyly, claw hands, microphthalmia and unusual association of gastrointestinal omphalocele.